Cumplimiento a la ejecución presupuestaria de la compañía Farmadescuento S.A. del cantón Vinces y su impacto a los estados financieros - Muñoz Teran, Lendhy Patricia (2021)
The company Farmadescuento S.A, is located in the city of Vinces, its commercial activity is the retail sale of pharmaceutical products through the blue cross pharmacies. This was founded on June 19, 2008. This is a job source for 277 to 2019. Within Farmadiscount the budget is made every year, and it is periodically reviewed in order to know and be able to measure its compliance; The executive manager is made known as well as the departmental heads so that in this way they can take it as a starting point for decision-making during the fiscal year. Farmadescuento S.A proposes goals of fulfillment in sales, commercial expenses (salaries, advertising, advertising, premiums, insurance), supplies, these are projections that at the end of the period determines whether or not the planned was fulfilled, in order to anticipate income and expenses involved in managing the business line. In review, it was mentioned the growth that Farmadescuento S.A has had in the period of 2019-2020 with 13.88%. its net margin increased 0.53% by 2020. In addition, by area, responsibilities, sales budgets, production, purchases, investments and expenses are realistically established, which can be achieved but simultaneously require significant effort from the areas involved. This implication of financial planning is a useful efficient and effective tool, providing a sustainable and sustainable development over time. Through planning we can validate the information within a set period in relation to financial statements versus budget planning. In conclusion, in terms of matter, for each department the estimate for part of the budget area must be linked to what is projected by each department in case of any modification, inform, as well as it is possible to determine new strategies or redirect objectives to more viable paths. An important point to highlight is that the budget is a very important tool since Farmadescuento S.A, is a company in the process of expansion with the monopolizing of the market at the national level.